Analysis of Justice in the Freelance Photographer Business (Takegon Central Aceh) - Manurung, Reneva; Purba, Bonaraja; Feby, Yohana (International Journal of Education, Information Technology, and Others, 2023)
Where this research is useful for teaching the general public, both young people who want to develop a career in the business world, because this young man from the Takegon area of Central Aceh already has his own motivation, the main thing is prayer and then determination which will be a big business and until now has a separate business venture which used to only have minimal money to start a business and has invested around IDR 50,000,000 starting from 2021 until now 2022, what a great achievement made by Rizky Fadly himself as a business owner who is currently still sitting at the university and has been able to win various awards ranging from certificates, certificates and coaching money both in the form of money for winning competitions, and also for the services of a photographer for other events so that he can open job vacancies for his friends around him and can also help retailers omian his parents. and where Ditakegon itself is still a lot of competitors in the world of photographers, but besides that, with the capital of ethics in establishing cooperation between clients and the quality of photographers from Imagehatch itself as the place of business of Rizky Fadly's brother, can make Imagehatch survive and can continue to grow.